Computer Sciences applied to Translation Undergraduate Programs in Public Universities in Argentina - Bianchini, Martha Inés (2018)
Since the nineties, the inclusion of technological components in the training of translators has been a need identified by translation professionals and academics. In this context, a cross-sectional exploratory study was proposed, aimed at looking into the inclusion of translation-applied computer sciences in the translation programs offered at public universities in Argentina, both in specific technology courses and in other curricular and extracurricular areas. Based on the information contained in documentary sources collected by the research project “Training in Translation and Interpretation in Argentina” (04/J025, UNComahue), and on the answers to questionnaires administered to the directors of the 18 study programs included, this article presents some preliminary conclusions: a minority of the study programs being researched contain a mandatory course on translation-applied computer sciences (no clear trends are identified as to the place of these courses in the study plans); lower complexity contents are discussed; the technologies are also discussed in other courses that are not specific to translation-applied computer technology. This analysis is the starting point for the deepening of knowledge of didactics of computer science applied to translation in Argentina in subsequent stages of this study.